Padronização da técnica de microdiluição em caldo e avaliação da sensibilidade antimicrobiana a óleos essenciais para isolados brasileiros de Brachyspira hyodysenteriae - Matheus Dias Araújo (2020)
The objective of this study was to standardize a new technique to evaluate the antimicrobial sensitivity of Brachyspira hyodysenteriae using the broth microdilution test comparing it to the commercial kit VetMIC™ Brachy SVA. In addition, the same broth test was used to evaluate the antimicrobial sensitivity of B. hyodysenteriae for the essential oils carvacrol, thymol and cynnamaldehyde. In order to do that, nine Brazilian strains, isolated between 2012 and 2019, and a reference strain, were harvested on agar, mantained under anaerobiosis atmosphere at 37°C during four days, resuspended in Brain Heart Infusion Broth with foetal bovine serum and inoculated under anaerobiosis atmosphere at 37°C during four days in 96 wells plates, doing serial dilution of the following antimicrobials: lincomycin, doxycycline, tiamulin, valnemulin and tylosin and the essential oils carvacrol, thymol and cynnamaldehyde. After four days, the antimicrobial sensitivity was evaluated by bacterial growth, visible through the media turbidity. For the commercial kit, manufacturer instructions were followed, adding 500 μl of the bacterial suspension to each plate well containing two-fold serial dilutions for lincomycin, doxycycline, tiamulin, tilvalosin, valnemulin and tylosin. The evaluation of sensitivity was performed as to the microdilution test. Our results demonstrated that the microdilution test can be a substitute to the commercial kit, having adequate similarity with each other, while the essential oils evaluated did not have satisfatory antimicrobial activity in vitro. Further in vivo studies are required to better understand their effects.